2023
DOI: 10.1002/bit.28384
|View full text |Cite
|
Sign up to set email alerts
|

Fully integrated downstream process to enable next‐generation manufacturing

Abstract: Next-generation manufacturing (NGM) has evolved over the past decade to a point where large biopharmaceutical organizations are making large investments in the technology and considering implementation in clinical and commercial processes.There are many well-considered reasons to implement NGM. For the most part, organizations will not fund NGM unless the implementation benefits the funding organization by providing reduced costs, reduced time, or additional needed capabilities. Productivity improvements gaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Examples include process intensification of the capture step by multicolumn chromatography (Coolbaugh et al, 2021; Kateja et al, 2021; Shi et al, 2021), the inclusion of a multicolumn chromatography capture step followed by connected polishing steps with ion exchange membrane adsorbers (Gjoka et al, 2017), continuous viral inactivation (Gillespie et al, 2019; Martins et al, 2020) and single‐pass TFF (Clutterbuck et al, 2017; Ding et al, 2022; Elich et al, 2019). Processes have more recently developed even further towards that of a fully integrated continuous downstream approach (Coolbaugh et al, 2021; Ramos et al, 2023). While these recent processes are not fully optimized, they do provide an excellent framework and proof of concept that has brought us ever closer to the end goal of true integrated continuous biomanufacturing.…”
Section: The Benefits Of Process Intensificationmentioning
confidence: 99%
“…Examples include process intensification of the capture step by multicolumn chromatography (Coolbaugh et al, 2021; Kateja et al, 2021; Shi et al, 2021), the inclusion of a multicolumn chromatography capture step followed by connected polishing steps with ion exchange membrane adsorbers (Gjoka et al, 2017), continuous viral inactivation (Gillespie et al, 2019; Martins et al, 2020) and single‐pass TFF (Clutterbuck et al, 2017; Ding et al, 2022; Elich et al, 2019). Processes have more recently developed even further towards that of a fully integrated continuous downstream approach (Coolbaugh et al, 2021; Ramos et al, 2023). While these recent processes are not fully optimized, they do provide an excellent framework and proof of concept that has brought us ever closer to the end goal of true integrated continuous biomanufacturing.…”
Section: The Benefits Of Process Intensificationmentioning
confidence: 99%
“…This strategy enabled achieving a constant concentration downstream of the capture step, regardless of the variability in titer during the run. 176 Karst et al demonstrated a feedback control system that modulates the capture step operating parameters of a countercurrent two-column capture based on at-line HPLC titer measurements. 177 Another key factor to consider when integrating upstream and downstream is the amount and composition of impurities generated during the upstream process.…”
Section: Integration Of Upstream and Downstream Processingmentioning
confidence: 99%